Photonic Crystal Palette of Binary Block Copolymer Blends for Full Visible Structural Color Encryption (Adv. Funct. Mater. 1/2022). (3rd January 2022) - Eoh, Hongkyu; Jung, Youngdoo; Park, Chanho; Lee, Chang Eun; Park, Tae Hyun; Kang, Han Sol; Jeon, Seungbae; Ryu, Du Yeol; Huh, June; Park, Cheolmin
Abstract : Block Copolymer Blends In article number 2103697, Cheolmin Park and co‐workers develop a palette of block copolymer photonic crystal inks, enabling convenient modulation of the structural color in the full visible range via solution blending of two lamellar‐forming block copolymers. The binary blend photonic crystals are applicable to various solution processes and offer efficient reflection‐mode pattern encryption suitable for emerging vision encryption technology requiring ultra‐thin, mechanically flexible, and thus skin‐patchable performance.